Enhancing Women’s Participation in Literacy Education Programmes in Niger State (Unilorin Journal of Lifelong Education, 2025)
This study was conducted to determine ways of enhancing women’s participation in literacy education programmes in Niger State. Five research questions were raised to achieve the objectives of the study. The study adopted the ex-post facto research design. The population of the study consists of two hundred and thirty-two (232) registered adult learners in three (3) literacy centres in Kotangora local government area of Niger State. The sample for the study consists of two hundred and thirty-two (232) registered adult learners in three (3) literacy centres in Kotangora local government area of Niger State. This study made use of a self-constructed closeended questionnaire. The validity of the instrument was determined using the face and content validity approach while the test re-test reliability approach was used to determine the reliability of the questionnaire. Data from the study were analysed using mean, frequency count and simple percentage. Findings from the study revealed that basic, advanced and functional literacy programmes are available for women, women’s participation in literacy education programmes can be enhanced through increased awareness creation, flexibility of programme, employment of female facilitators, free literacy books, Husbands permitting their wives to go literacy classes, and making literacy programmes compulsory for women. In view of the findings and conclusions from the study, it was recommended amongst others that literacy centre managers and facilitators should embark on wide-reaching awareness campaigns through different groups like traditional rulers, religious leaders and market places.